Efek Tryadic Communication Pura Samuantiga Dalam Pemujaan Tri Murti Di Bali - I Wayan Wirta; Sintyananda Gayatri (Jurnal Penelitian Agama Hindu, 2022)
There has been a conflict of understanding among Hindu religious groups, as a result of not adapting to the local cultural environment that has been considered well established. So as a consequence, there is a gap/conflict of understanding that has an impact on miscommunication. The concerns of various parties, especially among traditional Hindu figures as the "opinion leader" of Hindu communities in Bali with the concept of the teachings of "Tri Murti" insist on fortifying the influences of sampradaya teachings that are considered not in line with the tradition of "Dresta Bali". The effect of tryadic communication with the concept of Tri Murti teachings and the formation of pakraman villages/Balinese customary village is a strategic effort to anticipate, fortify and overcome conflicts between Hindu Religious groups, both at the pakraman village/customary village level and the family environment in Bali. The study used “dependency theory” from Ball-Rokeach and DeFlour. The method of data collection is participatory observation, in-depth interviews and literature studies. Data processing methods are carried out through processes : reduction, display and data verivikation. While the technique of determining informants is done purposive sampling. As for the findings of this study that the name "Pura Kahyangan Tiga" does not describe the number of appropriate temples that should amount to three in each village pakraman/customary village, but the fact in the field is different, it could be that one village pakraman/customary village has two temples (if Pura Desa/Bale Agung and Pura Puseh combined in one area) and even the number of Pura Kahyangan Tiga can be more than three pieces (if Pura Dalem Setra more than one). Therefore, it needs to be reviewed, the naming of Pura Kahyangan Tiga which is not in accordance with the concept in question. Based on this description, several conclusions can be drawn, namely : 1) Tryadic communications is “a triangular communication” (samuantiga) which in its implementation has caused the effect of Tri Murti in Bali, both at the family level, pakraman village/customary village and more broadly at Pura Sad Kahyangan for all Hindu communities in Bali. 2) The effect of tryadic communications Pura Samuantiga on the level of pakraman village/customary village was built Pura Kahyangan Tiga, which consists of : Pura Desa/Bale Agung as a place of worship of Lord Brahma, Pura Puseh as a place of worship of Lord Visnu and Pura Dalem as a place of worship of Lord Siva, as well as a unifying medium for all Hindus in the territory/territorial wewidangan pakraman village/customary village. 3) The effect of tryadic communications Pura Samuantiga on the family sphere was built Palinggih Kamulan Rong Telu/Tiga, as a medium of worship Tri Murti and the ancestral spirit of the siddhadewata, as well as a unifying media in the family sphere.